Aucubin Promotes Neurite Outgrowth in Neural Stem Cells and Axonal Regeneration in Sciatic Nerves - Kim, Yong Min (The Korean Society for Brain and Neural Science, 2014)
Aucubin is an iridoid glycoside with a wide range of biological activities, including anti-inflammatory, anti-microbial, anti-algesic as well as anti-tumor activities. Recently, it has been shown that aucubin prevents neuronal death in the hippocampal CA1 region in rats with diabetic encephalopathy. In addition, it has protective effects on H(2)O(2)-induced apoptosis in PC12 cells. We have shown here that aucubin promotes neuronal differentiation and neurite outgrowth in neural stem cells cultured primarily from the rat embryonic hippocampus. We also investigated whether aucubin facilitates axonal elongation in the injured peripheral nervous system. Aucubin promoted lengthening and thickness of axons and re-myelination at 3 weeks after sciatic nerve injury. These results indicate that administration of aucubin improved nerve regeneration in the rat model of sciatic nerve injury, suggesting that aucubin may be a useful therapeutic compound for the human peripheral nervous system after various nerve injuries.